2009
DOI: 10.1111/j.1600-0722.2009.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

A new osteopetrosis mutant mouse strain (ntl) with odontoma‐like proliferations and lack of tooth roots

Abstract: A new spontaneous mouse mutant (ntl) with autosomal-recessive osteopetrosis was characterized. These mice formed tartrate-resistant acid phosphate (TRAP)-positive osteoclasts but their osteoclasts had no ruffled border and did not resorb bone. These mice displayed no tooth eruption or tooth root formation. Adult mutant mice developed odontoma-like proliferations near the proximal ends of the incisors. Intraperitoneal injection of progenitor cells from the liver of 16.5 days postcoitum wild-type embryos into ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…WT = Wild-type. mouse lines [for review, see Helfrich, 2005], the dental phenotype has been established as being a direct consequence of osteoclast dysfunction [Yoshino et al, 2003;Lu et al, 2009]. Taken together, these experiments and the present study lend support to the concept that osteoclasts exert a 'microenvironmental' action on dental cells, although the underlying mechanisms are currently unknown.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…WT = Wild-type. mouse lines [for review, see Helfrich, 2005], the dental phenotype has been established as being a direct consequence of osteoclast dysfunction [Yoshino et al, 2003;Lu et al, 2009]. Taken together, these experiments and the present study lend support to the concept that osteoclasts exert a 'microenvironmental' action on dental cells, although the underlying mechanisms are currently unknown.…”
supporting
confidence: 74%
“…This phenotype was moderate here in Msx2-/-mice where the third molar was principally affected. In a more variable pattern, alterations to odontogenesis have been described; the defects include a complete lack of root formation, as observed in several mouse mutants [Lu et al, 2009], and/or, as shown in Msx2-/-mice in the present study, late growth of odontogenic tumor-like structures [Nakajima et al, 1996;Tiffee et al, 1999], the occurrence of which is frequently reported. It may involve continuously erupting incisors and/or limited growth of molars.…”
mentioning
confidence: 85%
“…Recent animal testing revealed that a specific gene variation in root odontoblasts is able to affect root formation. 34 The genes Nfic, 35 Msx2, 36 Shh, 37 Sp6, 38 Noggin, 39 b-catenin, 40 smadd4, 41 Ntl, 42 and Rankl 43,44 are related to the shape, length, and number of roots. Among these, the most relevant to the present study is the Wnt/b-catenin signaling associated with root and cementum formation.…”
Section: Oral and Maxillofacial Pathology Oooomentioning
confidence: 99%
“…However, tooth eruption is a complex process that also requires the combined influences of dental follicle, periodontal ligament, hydrostatic pressure and root formation (Helfrich, 2005;Tiffee et al,1999). So far, lack of tooth root formation has been observed in four osteopetrosis models, namely ntl mice (spontaneous mutant mice), Rank À/À mice, Rankl À/À mice, and c-src À/À mice (Lu et al, 2009;Tiffee et al, 1999). A clinical report described an ARO patient with some teeth without root development (Jalevik et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…We suspected that ClC-7 has a spatial and temporal distribution during mouse tooth development and might contribute to the mouse tooth development (Su et al, 2008). It is widely believed that the Hertwig's epithelial root sheath probably initiates differentiation of odontoblasts from the peripheral mesenchymal cells followed by tooth root formation (Lu et al, 2009). Recently it was demonstrated that osteoclasts play an essential role in root formation (Lu et al, 2009) and it is possible that ClC-7 in different tooth cells could contribute directly to the root formation.…”
Section: Discussionmentioning
confidence: 99%